A proposed revised textbook for Grade One: God Loves Me, and teacher's manual - Juanillo, Eden S. (Animo Repository, 1994)
This research focuses on developing catechism through the use of Narrative Theology or Story Theology. The approach realigns the methodology in catechetical instruction based on the recommendations of the National Catechetical Directory of the Philippines (NCDP).This thesis clarified, updated, and provided some topics and activities. Prior to actual revision, the existing Religion textbooks as well as the available Teacher's manuals were evaluated. In the revision process, pertinent questions and priority areas were identified. Manuals were, then, prepared.The proposed revised textbook featured the use of stories as the main strategy in imparting contents, attitudes, and skills based on the principles of Narrative Theology. Among the kinds of stories used were Bible Stories, lives of saints, fairy tales, Filipino stories, and folk tales.Integrated with the lessons were Filipino and Gospel values, devotion to Mary and the saints, peace, and economy. An appropriate number of activities challenged the learners to live the faith. Biblical stories and verses made learning to be scripturally-based.It is recommended that religious textbooks and manuals be evaluated and updated according to the needs of Filipino learners and catechists. Continuous formation of catechists should be done in schools, parishes, and the regions. Reference materials on the Catholic doctrines should be available for the Catechism teacher's use.